Analisis Kapasitas Antioksidan dan Sensori Minuman Serbuk Anggur Laut sebagai Terapeutik Obesitas: The Analysis of Antioxidant Capacities and Sensory in Sea Grapes (Caulerpa racemosa) Powdered Drink as a Therapeutic Obesity - Dwi Santy Damayati; Evy Damayanthi; Hadi Riyadi; I Wayan Teguh Wibawan; Ekowati Handharyani (Amerta Nutrition, 2023)
Background: Obesity is a global problem which increasing simultaneously. The high-fat accumulation in the body will result from mild chronic inflammation. Developing a local drink based on seagrapes (Caulerpa racemose) is thought to have a high antioxidant capacity and the potential to become an alternative therapeutic drink for obese people. Seagrapes are easily damaged, so proper drying is needed to maintain antioxidant potential and assisted by adding gum arabic to increase the acceptability. Objectives: To analyze the antioxidant capacity and sensory of sea grapes powder drink (Caulerpa racemose). Methods: The design experiment research was utterly randomized and only used one gum Arabic treatment with a 2.5, 5, and 10% concentration and three replication as sea grapes powder drink samples. The samples were analyzed to seek the antioxidant capacity of DPPH (2,2-diphenyi-1-picrylhydrazyl), CUPRAC (Cupric Ion Reducing Antioxidant Capacity), and FRAP (Ferric Reducing Antioxidant Power). Then research data were analyzed by employing ANOVA  and Duncan's follow-up test. Results: The higher concentration of gum Arabic has significantly increased the antioxidant capacity. DPPH, CUPRAC, and FRAP values in 10% gum Arabic concentration were 13.21±0.1 mg/100 g, 25.26±0.5 mg, and 2.89±0.3mg/g. Based on the sensory test results, the panelists preferred the 10% gum Arabic concentration because the color is lighter, can minimize odor and viscosity, and taste better. Conclusions: Seagrapes powder drink with a concentration of 10% gum Arabic has the potential as a therapeutic obesity with the highest antioxidant capacity and is sensory acceptable.